Enhanced piezoelectric output performance via control of dielectrics in Fe2+-incorporated MAPbI3 perovskite thin films: Flexible piezoelectric generators. (July 2018) - Ippili, Swathi; Jella, Venkatraju; Kim, Jaegyu; Hong, Seungbum; Yoon, Soon-Gil
Abstract: We report a high-performance flexible piezoelectric generator (PEG) that was based on organic-inorganic lead halide perovskite materials and is operated by controlling the dielectric constant via the partial substitution of Pb 2+ with Fe 2+ in MAPbI3 . The partial replacement of Pb 2+ with Fe 2+ improved both the morphology and crystallinity of MAPb1-x Fex I3 (0.01 ≤ x ≤ 0.50) films that undergo a tetragonal-cubic phase transition above an incorporated concentration of Fe 2+ (x > 0.07). In addition, the phase transition temperatures of MAPb1-x Fex I3 (0.01 ≤ x ≤ 0.07) films linearly decreased as a function of incorporated concentration, which resulted in a transition temperature for MAPb1-x Fex I3 (x = 0.07) of 45.5 ± 1.5 °C. The dielectric properties as a function of incorporated concentration at room temperature suggested that MAPb1-x Fex I3 (x = 0.07) exhibited a dielectric constant of 107 and a dissipation factor of 0.02 at 100 kHz. The MAPb1-x Fex I3 (x = 0.07) films exhibited a low leakage current density of 10 −6 at a high applied electric field of 40 kV/cm, and the resultant remanent polarization from saturated ferroelectric P-E hysteresis loops was 1.6 µC/cm 2 . The MAPb1-x Fex I3 (x = 0.07) flexible PEG improved output performance by 7.29 V and current density by 0.88 µA/cm 2 after poling at 30 kV/cm. This was sufficient to instantly light a commercial light-emitting diode (LED) without a storage device. This approach provides a framework that enhances the output performance of organic-inorganic metal halide perovskite materials-based piezoelectric energy harvesters, which could help pave the road to viable, self-powered, wearable electronics. Graphical abstract: The partial replacement of Pb 2+ with Fe 2+ in MAPbI3 perovskite films showed the significant improvement in dielectric properties as well as piezoelectric output performance at the dopant range of x = 0.07. In particular, high-performance flexible piezoelectric generator was fabricated using MAPb1-x Fex I3 (x = 0.07) perovskite film. The output voltage and current density of PEG were 7.29 V and 0.88 µA/cm 2, respectively.fx1 Highlights: High performance flexible piezoelectric generator using MAPb1-x Fex I3 (0.01 ≤ x ≤ 0.07) films. Phase transition temperature of MAPb1-x Fex I3 (x = 0.07) is 45.5 ± 1.5 °C. MAPb1-x Fex I3 (x = 0.07) films having a predominate dielectric property. MAPb1-x Fex I3 (x = 0.07) PEG having output voltage of 7.29 V and current density of 0.88 µA/cm 2 . Instantly lightening of a commercial light-emitting diode (LED) without a storage device.